2007
DOI: 10.1056/nejmsa062860
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Management of Chronic Disease at Community Health Centers

Abstract: The Health Disparities Collaboratives significantly improved the processes of care for two of the three conditions studied. There was no improvement in the clinical outcomes studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
181
2
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 241 publications
(193 citation statements)
references
References 20 publications
7
181
2
3
Order By: Relevance
“…1 Achieving blood pressure control (BP) in patients with hypertension reduces the risk of stroke and ischemic heart disease. [2][3][4] Despite everincreasing public health resources dedicated to improving BP control, [5][6][7] only half of the 78 million Americans with hypertension have their BP treated and controlled to the recommended value of below 140/90 mmHg. 8 Under new BP targets recommended by the Panel Members Appointed to the Eighth Joint National Committee (JNC 8), 9 BP is controlled in less than 60 % of hypertensive patients overall, and in less than 50 % of patients younger than 60 years of age.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Achieving blood pressure control (BP) in patients with hypertension reduces the risk of stroke and ischemic heart disease. [2][3][4] Despite everincreasing public health resources dedicated to improving BP control, [5][6][7] only half of the 78 million Americans with hypertension have their BP treated and controlled to the recommended value of below 140/90 mmHg. 8 Under new BP targets recommended by the Panel Members Appointed to the Eighth Joint National Committee (JNC 8), 9 BP is controlled in less than 60 % of hypertensive patients overall, and in less than 50 % of patients younger than 60 years of age.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 However, quality improvement efforts in other clinical settings have failed to achieve similar success. 5 A better understanding of the expected relative effectiveness of different types of interventions could inform public health efforts and facilitate a more cost-effective use of resources.…”
Section: Introductionmentioning
confidence: 99%
“…36,[42][43][44] Recent chart audit studies showed inconsistent improvement in A1c, BP, and LDL, depending on the length of the period after the initiative. 16,[45][46][47] This study had a relatively short period after the program (1 year), yet significant improvements were found. Future research could employ a longer period to examine the impact over time and to determine the spread and sustainability of the results reported herein.…”
Section: Discussionmentioning
confidence: 91%
“…Overweightness and obesity continue to rise among both adults and children, increasing the prevalence of chronic diseases in both groups. Multiple programs have been initiated to combat these health disparities, with differing levels of success [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In 2007, Landon [9] reported on a study of care at community based health clinics examining patients with diabetes, asthma and hypertension. These health clinics instituted quality improvement methods to change patient care.…”
Section: Introductionmentioning
confidence: 99%